Toxicological and demographic patterns in poisoning fatalities: a retrospective study at AIMS, B. G. Nagara - Gopala, Sandhya; Mahadeva, Rakshitha Balenahalli; Yelauri, Chinmayi; Govindegowda, Vijay Kumar Aralapura (International Journal of Research in Medical Sciences, 2025)
Background: Poisoning related fatalities represent a major global health concern, contributing to a substantial number deaths each year. Identifying mortality trends from such poisoning is fundamental to designing effective preventive and remedial strategies. The objective of study aims to examine the autopsy profile of poison related fatalities at AIMS, BG Nagara, India. Methods: This study is 4 years retrospective case record analysis of a population comprising suspected poison cases brought for autopsy. The cases with suspected poisoning, confirmed through clinical evaluation or chemical analysis, were included in the study. Results: During the study period, a total of 395 cases were examined, of which 113 (28.6%) were confirmed cases of poisoning. Among these, 90 cases (79.60%) involved males, while 23 cases (20.40%) involved females. The most affected age group was 31-50 years, accounting for 41 cases (36.30%). Regarding the manner of death suicidal poisoning was predominant, with 101 cases (89.40%), whereas accidental poisoning accounted for 12 cases (10.60%). Forensic chemical analysis (FSL) yielded positive identification of poisons in 84 cases (74.30%). Among the identified poisons, organophosphates poisoning was the most prevalent, observed in 57 cases (50.40%). The predominant survival duration prior to death was between one day and one week, observed in 55 cases (48.07%). Seasonal variation analysis showed minimal differences, with peak 29 cases (25.60%) recorded between September and November. Conclusions: Poisoning is a major health issue, especially among middle-aged men, often linked to suicide. Better safety, mental health care and testing can help reduce deaths and improve public health.